The role of a captopril renal scintigraphy in examination of children with hypertension – A case report - Milošević, Biljana; Žeravica, Radmila; Grebeldinger, Slobodan; Vukmirović Papuga, Marija; Ilić, Dalibor (Vojnosanitetski pregled, 2021)
Introduction. Secondary hypertension is a relatively common form of hypertension in childhood with renovascular hypertension being responsible for 5%–10% of all arterial hypertensions in children. An early diagnosis of renovascular hypertension is important when considering an appropriate treatment of hypertension that may prevent or slow further progression of kidney damage. To validate the usefulness of a captopril renal scintigraphy in hypertensive children, we report a case of a 16-year-old female patient with a history of hypertension as a result of fibromuscular dysplasia. Case report. The patient was asymptomatic with elevated blood pressure revealed by a routine physical examination. Laboratory tests showed the increased levels of plasma renin activity with the normal levels of aldosteron. The renal ultrasound was normal. The Doppler of the renal arteries showed no significant differences of resistive index. A renal captopril scintigraphy was performed, including two day study protocol, the baseline study followed by another captopril study several days later. The scintigraphy showed the abnormal baseline and captopril renogram curve of the right kidney with significant cortical retention of radiotracer after angiotensin-converting enzyme inhibition. Following the captopril scintigraphy a renovasography was obtained confirming the presence of a 2 mm long circular narrowing of the right renal artery. It was immediately treated resulting in a significant expansion of the lumen. Conclusion. The captopril renal scintigraphy allows non-invasive functional testing in a selected group of hypertensive children, which can either confirm or rule out the existence of hemodynamically significant renal artery stenosis.